Claire Vivés, L’institutionnalisation du recours aux opérateurs privés de placement au cœur des conflits de régulation du service public de l’emploi (2003-2011) - Claire Vivés (Revue de la Régulation)
This research leans on public policy analysis, industrial relations theory and economic sociology. It demonstrates the introduction and institutionalization of competition within public employment service despite the fact the claimed greater effectiveness of private providers is not proved.Violent controversies appeared around these markets of outsourcing of placement services. They enlighten conflicts about PES regulation which terms are modified by institutional architecture evolutions. Before the merge (2008), outsourcing is a weapon for the institution jointly managed by employee and employer representatives against the public agency (ANPE). After 2008, the public operator re-appropriates externalisation to mobilize it as an adjustment variable, sign of its dominant position close to a new monopoly.